New alternative proposal in physical education: Touchtennis as a racket sport in schools - Morales-Campo, Paula Teresa; Pérez-Muñoz, Salvador; López-García, Sergio; Díez-Fernández, Pelayo; Rodríguez-Cayetano, Alberto (Frontiers in Sports and Active Living, 2025)
In the last decade, the subject of Physical Education has undergone significant transformations, exploring new teaching alternatives for students to acquire interest and enthusiasm for sport. The main objective of this descriptive study is to bring Touchtennis to schools as an innovative and alternative racket sport, which has attracted interest in the sports field. In terms of methodology, an intervention proposal is presented, designed for the subject of Physical Education, through a methodological sequence, in order to get to know the basic contents of the sport and to improve the physical, psychological, social and emotional components of the student. To date, Touchtennis lacks scientific evidence to support its effects. Consequently, a pedagogical proposal is presented in order to open up a promising field for future research, which could reveal its potential in the educational and sporting sphere. It is therefore essential that, on the basis of this research, empirical tests are carried out to analyse the effect of this sport.